The utility of open-access biodiversity information in representing anurans in the Brazilian Atlantic Forest and Cerrado - Vasconcelos, Tiago da Silveira [UNESP]; Nascimento, Bruno Tayar Marinho [UNESP] (Melopsittacus Publicacoes Cientificas Ltd, 2014)
Many geographic coordinates of species are only available in biological collections, and sometimes it is difficult to access these data. However, recent initiatives promise to compile and organize such biodiversity data at a global scale. We evaluated the effectiveness of open-access biodiversity information for forecasting the occurrence of anurans in two Brazilian hotspots - the Atlantic Forest (AF) and the Cerrado (CER). We compiled all available point-occurrence records for anuran species in both hotspots and identified the regions in each of the two hotspots having the highest and lowest number of anuran occurrences based on information from the Global Biodiversity Information Facility (GBIF) and the Species Link project. A total of 13,130 point-occurrence records were recovered for 409 anurans from the AF (similar to 77% of the known species) and 12,729 records for 176 species (similar to 85% of the known species) from the CER. Density of point occurrence data is not randomly distributed within the hotspots. The greatest density of Atlantic Forest records is in southeastern Brazil, and the densest areas in Cerrado occur in the transitional zones to the Atlantic Forest. Comparison of these results with previous studies based on traditional museum information revealed that many important collections of anurans from these hotspots are not included in GBIF and SpeciesLink.

Muitas coordenadas geográficas de espécies estão disponíveis apenas em coleções biológicas, sendo muitas vezes de difícil acesso. No entanto, existem iniciativas recentes para compilar e organizar esses dados de biodiversidade em escala global. Nós avaliamos a efetividade dessas ferramentas gratuitas de acesso à informação biológica para representar a ocorrência de anuros nos hotspots brasileiros Cerrado (CER) e Mata Atlântica (MA). Nós compilamos os registros de pontos de ocorrência de todas as espécies disponíveis em ambos os hotspots e identificamos regiões com alta e baixa representatividade de ocorrências de anuros para ambos os hotspots utilizando duas ferramentas gratuitas de busca por informação biológicas (The Global Biodiversity Information Facility - GBIF; projeto SpeciesLink). Foram registrados 13130 pontos de ocorrência para 409 anuros da Mata Atlântica (~77% das espécies conhecidas) e 12729 pontos para 176 espécies do Cerrado (~85% das espécies conhecidas). A densidade dos pontos de ocorrência não está distribuída aleatoriamente ao longo de ambos os hotspots. A maioria dos registros da MA está concentrada no sudeste do Brasil, sendo que as áreas mais densas no CER ocorrem em áreas de transição com a MA. Comparando com estudos prévios que utilizaram dados de coleções não implementadas nas ferramentas utilizadas neste estudo, concluímos que o GBIF e SpeciesLink não hospedam coleções biológicas importantes para anfíbios do CER e MA.
A utilidade de informações de livre acesso à biodiversidade para a representatividade de anuros da Mata Atlântica e Cerrado brasileiro
Keywords: Amphibians; GBIF; Point density analysis; SpeciesLink; Anfíbios; Análise de densidade pontual; GBIF; SpeciesLink